The Policy of Bureaucratic and Agrarian Reorganization in Madura until the End of the Nineteenth Century - Iswahyudi Iswahyudi (Budapest International Research and Critics University, 2021)
The traditional agrarian and government bureaucracy system in Madura by placing the role of panembahan is the same as the sultan in Mataram who is considered to have a central position both politically, socially and culturally as well as religiously. Since the mid-19th century on the part of the Dutch East Indies government, there have been indications to realize a change in the bureaucratic system which was originally patrimonial to be rational. The only thing that can be used as a tool to act, is the existence of a constitutional policy of the Dutch kingdom regarding the management of colonized areas, namely the issuance of a Government Regulation in 1854. The success of the Dutch government in reorganizing the bureaucracy and agrarian in Madura by dividing it into four districts, namely Bangkalan, Sampang, Pamekasan, and Sumenep are short-term strategies.